Values of axial age - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article shows that the period of axial age (VIII–II centuries BC), as K. Jaspers defined it, was a time of deep understanding of the fundamental truths of human existence. Great thinkers of this period overcame rigid patrimonial, ethnic and sacred traditions of behavior and chose freely new values that became moral milestones of the life of people afterwards. It is possible to identify similar basic moral values, orientation to humanity in the ideas of the founders of Zoroastrianism, Confucianism, Taoism, Hinduism, Buddhism, prophets in the Bible, Greek philosophical schools, and later on Islam, with a certain difference of views on the ways of realization of these values.
Keywords: axial age; self-reflection; value choice; Zoroastrianism; Confucianism; Taoism; Hinduism; Buddhism; prophets in the Bible; Greek philosophy; Islam